Carbonic anhydrase/formate dehydrogenase bienzymatic system for CO2 capture, utilization and storage. Issue 1 (22nd October 2021) - Sato, Ryohei; Amao, Yutaka
Abstract : In order to establish carbon capture, utilization, and storage (CCUS) technology, a system consisting of two different biocatalysts (formate dehydrogenase from Candida boidinii ; CbFDH and carbonic anhydrase from bovine erythrocytes ; CA) is developed. Abstract : In order to establish carbon capture, utilization, and storage (CCUS) technology, we focused on a system consisting of two different biocatalysts (formate dehydrogenase from Candida boidinii ; CbFDH and carbonic anhydrase from bovine erythrocytes ; CA). CA catalyses the interconversion between CO2 /water and dissociated bicarbonate ions/protons. CbFDH is a NAD + -dependent dehydrogenase that catalyzes CO2 reduction to formate by using the NAD + /NADH redox couple. The construction of a bienzymatic system consisting of CA and CbFDH (CA/CbFDH system) for a CCUS system was attempted. At 150 or 200 μM CA in the sample solution and a controlled pH of 6.3–6.5 by CO2 bubbling, due to the promotion of the conversion of CO2 to bicarbonate, the reaction rate for CbFDH-catalyzed CO2 reduction to formate decreased to about 50% as compared with that in the absence of CA. In the higher pH region (>9.5), despite the low CO2 concentration in this region, in contrast, it was found that the addition of CA promoted the reduction of CO2 catalyzed by CbFDH to formate to about 7 times higher than that under the conditions without CA. This shows that a CCUS system was constructed in which the conversion of bicarbonate to CO2 using CA and the reduction of CO2 to formate using CbFDH were coordinated.